External economies of scale, government purchasing commitment and welfare improvements in the vaccines industry - Garcia- (European Journal of Government and Economics (EJGE), 2012)
Some industries exhibit external economies of scale. In these cases,the introduction of self-financing tax subsidy programmes canimprove social welfare. This paper advocates intervention incompetitive markets if economies of scale existand implementing the policy is inexpensive.
Keywords: 330; external economies of scale; social welfare; tax-subsidy; income transfer; government intervention